Value chains for sustainable mountain development: a qualitative understanding of 23 European cases - Kirsty Blackstock; Rachel Creaney; Mar del Mar Delgado-Serrano; Sharon Flanigan; Corrado Ievoli; Michele Moretti; Gusztáv Nemes; Diana Surovà; Chloe Thompson; Lukas Zagata; Tarek Allali; Angelo Belliggiano; et al. (Journal of Rural Studies, 2025)

Actions to strengthen the contribution of small farms and small food businesses to food security in Europe - Olga M. Moreno-Pérez; Laura Arnalte-Mur; Pedro Cerrada-Serra; Victor Martinez-Gomez; Anda Adamsone-Fiskovica; Bjørkhaug; Gianluca Brunori; Marta Czekaj; Dominic Duckett; Paola A. Hernández; Christina Noble; Teresa Pinto-Correia; et al. (Food Security, 2024)
This study stems from a participatory foresight exercise conducted in nine Mediterranean, Baltic, Nordic and Eastern European regions, aiming to strengthen the role of small farms and small food businesses in ensuring food security. A wide range of stakeholders participated by attending workshops. They represented farmers’ organisations, food businesses, consumers’ organisations, NGOs, researchers, extension services, professional groups, and administration and public bodies. The actions proposed by participants are scanned and categorised around six broad objectives, stakeholders’ priorities and their underlying beliefs and preconceptions are discussed around the current debates of the literature, and the drivers that influence the feasibility of the proposed actions are discussed. Furthermore, the alignment of stakeholders’ -driven objectives with the European Strategies on food, agriculture, and rural areas is examined, with a focus on: (i) the EU Farm to Fork Strategy, (ii) the Rural Action Plan contained in the Long-Term Vision of Rural Areas developed by the EU Commission, and (iii) the Common Agricultural Policy in force since January 2023.

Oyster aquaculture cages provide fish habitat similar to natural structure with minimal differences based on farm location - Renee Mercaldo-Allen; Peter J. Auster; Paul Clark; Mark S. Dixon; Erick Estela; Yuan Liu; Lisa Milke; Gillian Phillips; Dylan Redman; Barry C. Smith; Alison Verkade; Julie M. Rose (Frontiers in Marine Science, 2023)
Oyster aquaculture gear may augment natural seafloor by providing structured habitat for economically important fish species. Underwater video census was used to assess fish abundance and community composition on eastern oyster ( Crassostrea virginica ) shelf and bag style aquaculture off-bottom cages and within natural rock reef habitat. During 2018, underwater cameras were mounted on four study cages at a dense shellfish farm of 40-100 commercial cages (dense cage farm), on four single cages interspersed on low relief seafloor (sparse cage farm), and amongst four boulders on a rock reef (rock reef), within an embayment off Milford, Connecticut, which is part of Long Island Sound, in the United States. In 2019, cameras were similarly deployed on two study cages per farm at each of three shellfish farms off Milford, Norwalk and Westport, CT. Video was recorded hourly in eight-minute segments from 7 am to 7 pm. Data loggers monitored seawater temperature, light intensity, and current speed. Fish abundance (MaxN) was calculated for all videos. We compared fish abundance and community composition between May and September, on cage and boulder habitat, on cages at dense and sparse farms and on cages across farm locations. In 2018, abundance of black sea bass ( Centropristis striata ), scup ( Stenotomus chrysops ) and tautog ( Tautoga onitis ) was significantly higher on cages than boulders, regardless of cage number. Cunner ( Tautogolabrus adspersus ) abundance was significantly higher on boulders than cages when cage sites were grouped. However pairwise comparisons indicated that cunner were significantly higher at the sparse cage farm versus the rock reef but cunner abundance on the dense cage farm and rock reef sites was not significantly different. Abundance of black sea bass, scup, tautog, and cunner were not significantly different across 2019 farm locations. Young-of-the-year fish occurred episodically at all sites during both years, with black sea bass and scup most abundant. Fish abundance corresponded to seasonal changes in seawater temperature and was highest at the warmest temperatures. Light intensity and current speed explained less variation in fish abundance relative to temperature, and relationships were inconsistent across habitats and farm locations Our results suggest that multi-tiered oyster aquaculture cages contribute structure to seafloor environments that provide habitat for temperate reef fish similar to natural rock reefs.

Competition between the gypsy moth, Lymantria dispar, and the northern tiger swallowtail, Papilio canadensis: interactions mediated by host plant chemistry, pathogens, and parasitoids - Ahnya M. Redman; J. Mark Scriber (Oecologia, 2000)

A polarized salivary cell monolayer useful for studying transepithelial fluid movement in vitro - Xinjun He; Gemma A. J. Kuijpers; Gertrud Goping; Jill A. Kulakusky; Changyu Zheng; Christine Delporte; Chung-Ming Tse; Robert S. Redman; Mark Donowitz; Harvey B. Pollard; B. J. Baum (Pflügers Archiv - European Journal of Physiology, 1998)